On Computation of Degree-Based Entropy of Planar Octahedron Networks - Tian-Le Sun; Haidar Ali; Bilal Ali; Usman Ali; Jia-Bao Liu; Parvez Ali (Journal of Function Spaces)
Chemical graph theory is the combination of mathematical graph theory and chemistry. To analyze the biocompatibility of the compounds, topological indices are used in the research of QSAR/QSPR studies. The degree-based entropy is inspired by Shannon’s entropy. The connectivity pattern such as planar octahedron network is used to predict physiochemical activity. In this article, we present some degree-based entropies of planar octahedron network.